2021
DOI: 10.1186/s12893-021-01229-9
|View full text |Cite
|
Sign up to set email alerts
|

A rare cutis verticis gyrata secondary to cerebriform intradermal nevus: case report and literature review

Abstract: Background Cutis verticis gyrate (CVG) is a rare morphologic syndrome that presents with hypertrophy and folding of the scalp. CVG can be classified into three forms: primary essential, primary non-essential, and secondary. Cerebriform intradermal nevus (CIN) is a rare cause of secondary CVG. We are here to report a rare case of CVG with an underlying CIN and discuss the clinical course, treatment options, and critical screening guidelines for these patients. Case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…[6] e average number of skin folds with CVG in one study was six, though it may vary from two to as many as twenty folds. [7] e direction of the folds is usually anterior to posterior in vertex but may be transverse over the occipital region or sometime can be irregular. In primary CVG, folds are usually symmetrical and are asymmetrical in secondary form.…”
Section: Discussionmentioning
confidence: 99%
“…[6] e average number of skin folds with CVG in one study was six, though it may vary from two to as many as twenty folds. [7] e direction of the folds is usually anterior to posterior in vertex but may be transverse over the occipital region or sometime can be irregular. In primary CVG, folds are usually symmetrical and are asymmetrical in secondary form.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to report CVG secondary to neurofibroma, folliculitis fibrosis, dissecting cellulitis, and lipoedema. Previous studies reported CVG secondary to acromegaly (14,15) , cerebriform intradermal nevus (2,3) . We were unable to find the primary non-essential form of CVG, which is rare and exceptional.…”
Section: Discussionmentioning
confidence: 99%
“…The primary essential CVG is not linked to any other diseases, whereas the primary nonessential form is linked to mental deficiency, neurological diseases, and ophthalmological disorders (2) . Secondary CVG can be caused by many factors, including inflammatory dermatoses, systemic diseases, infiltrates, and cutaneous neoplasms (3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, Cutis verticis gyrata (CVG) is a rare scalp condition characterized by excessive subcutaneous tissue proliferation, resulting in folds resembling cerebral gyri. 1 First docu-mented by Jean-Louis-Marc Alibert in 1837 and later named by Paul Gerson Unna in 1907, it is also known by various names like Robert-Unna syndrome, bulldog scalp, and corrugated skin. The estimated prevalence rate in adults is 1 in 100 000 for men and 0.026 in 100 000 for women.…”
mentioning
confidence: 99%